CRANIOSYNOSTOSIS: EARLY RECOGNITION PREVENTS FATAL COMPLICATIONS - Raja, Raja RA; Khemani, Khemani VD; Sheikh, Sheikh S; Khan, Khan H (Journal of Ayub Medical College Abbottabad, 2011)
Background: Craniosynostosis is the premature fusion of cranial vault sutures. The overall incidence is 3-5/10,000 live births. With multiple craniosynostoses, brain growth may be impeded by the unyielding skull. Most cases of single suture involvement can be treated with linear excision of suture. Involvement of multiple sutures or skull has usually required combined efforts of neurosurgeons and craniofacial surgeons. Methods: On the basis of visible skull deformity all patients were admitted in the Department of Neurosurgery, Liaquat University Hospital, Jamshoro, Pakistan. Patients were examined for signs of raised ICP and other congenital deformities. The records of patients were maintained till follow up. Results: Twenty-seven children were included in this study from 2002 to 2009. Age range was 1-6 years, boys were 18 (66.6%), and girls were 9 (33.3%). The common suture affected was coronal 12 (44.4%). Two children with craniostenosis belonged to same family, and all presented with suture involvement. Three (11.1%) deaths occurred due to hypothermia (1), and blood loss (2). Conclusion: Early diagnosis, expert surgical techniques and per- and postoperative care for bleeding and temperature regulation prevent mortality and morbidity. Keywords: Craniosynostosis, children, skull defects, suture